Effect of Pei Yuan Tong Nao capsules on neuronal function and metabolism in cerebral ischemic rats. (28th June 2019) - Bai, Jing; Gao, Ying; Gao, Yong-Hong
Abstract: Ethnopharmacological significance: Pei Yuan Tong Nao (PYTN) capsules have been used in traditional Chinese medicine (TCM) for many centuries for the treatment of renal and vascular diseases, including cerebral ischemia. Although they are used in clinical practice, the evidence of their efficacy is lacking. Materials and methods: The cerebral ischemic rat model was established by bilateral carotid artery ligation and shear surgery. The laser speckle blood flow imaging apparatus was used to observe the changes in cerebral blood flow before and after surgery. The working memory of rats were analyzed using the Morris water maze (MWM) test. The 2-deoxy-2-[ 18 F]fluoro-D-glucose (18-FDG) standard uptake values (SUVs) of rats with cerebral ischemia were evaluated by small-living animal positron emission tomography (PET) imaging. The quantity of acetylcholine in the hippocampus and the protein quantity of α7 nicotinic acetylcholine receptor in the hippocampus were detected with high-resolution fluid phase chromatography and Western blot analysis. Results: There was no significant difference in the preoperative mean cerebral blood perfusion between the groups. There was a significant decrease ( P  < 0.01) in cerebral perfusion in the model-operation, nimodipine, and PYTN groups after bilateral common carotid artery occlusion (BCCAo) compared with presurgery. The escape latency is shortened in the PYTN group ( P  < 0.05) compared with the model-operation group. SUVs of the nimodipine and PYTN groups increased ( P  < 0.05) compared with the model-operation group. After treatment with nimodipine and PYTN, acetylcholine levels in the hippocampus of the rats in the respective groups were lower than that of the sham-operation group ( P  < 0.01), and acetylcholine levels in the hippocampus of the nimodipine and PYTN groups were higher than that of the model-operation group ( P  < 0.05). α7 nicotinic acetylcholine receptor analysis showed that the protein levels of the nimodipine and PYTN groups increased after treatment compared with the model-operation group ( P  < 0.05). Conclusion: PYTN capsules improved the performance of rats with cerebral ischemia (analyzed using the MWM test), which may be due the to improvement of glucose metabolism in the hippocampus (evaluated by estimating acetylcholine and α7 nicotinic acetylcholine receptor protein). Graphical abstract: Image 1